Acquired Amegakaryocytic Thrombocytopenia and Pure Red Cell Aplasia in Thymoma - Sumit Dahal; Eliza Sharma; Suyash Dahal; Binav Shrestha; Bikash Bhattarai (Case Reports in Hematology)
Association of thymoma with myasthenia gravis, pure red cell aplasia, and aplastic anemia is well documented. However, thymoma complicated by acquired amegakaryocytic thrombocytopenia (AAMT) is rarely reported. Here, we present a case of a 60-year-old male with past medical history of recurrent invasive thymoma who presented with cough and blood in sputum. He was found to have severe normocytic normochromic anemia and thrombocytopenia that did not improve with intravenous steroids or multiple transfusions of red cells and platelets. Subsequent bone marrow biopsy showed severely depleted megakaryocytes and erythroid precursor cells with relative myeloid hyperplasia suggestive of amegakaryocytic thrombocytopenia and red cell aplasia. He was started on oral cyclosporine but subsequently developed leukopenia and refused any further treatment or diagnostic procedures and left the hospital against medical advice. AAMT, thus, may be a very early presentation of impending aplastic anemia, and treating physicians need to be aware of this entity.